World Practice of Using Biogas as Alternative Energy - Tasmaganbetov, Aslan B.; Ataniyazov, Zhumabay; Basshieva, Zhangul; Muhammedov, Abu U.; Yessengeldina, Anar (International Journal of Energy Economics and Policy, 2020)
The article evaluates the biogas as the alternative energy source useful for contributing to the future. Biogas has been found to offer one of the best alternatives due to its economic significance as well as the improved sustainable development through reduced greenhouse gas emissions. The work investigates the production of biogas as an alternative source of energy while outlining its significance in reducing the issues of power energy as well as environmental pollution. The authors analysed the level of bioenergy development in Kazakhstan and around the globe. They revealed that Brazil, China, USA, India and Germany are leaders of bioenergy production in the world. According to the authors, development of bioenergy in Kazakhstan is related to commissioning of new bioenergy stations and supporting sources of renewable energy by government mechanisms. In the case of Kazakhstan, the authors highlighted the fact that existing biogas plants are only used for processing municipal solid waste in urban landfills despite being a major producer of agricultural products. Keywords: Alternative Energy Source, Bioenergy, Green Economics JEL Classifications: Q42, Q50 DOI: https://doi.org/10.32479/ijeep.9805